Pyoderma Gangrenosum: A Rare Cause of Cutaneous Ulceration and One Easily Misdiagnosed. (21st September 2016) - Abdelrahman, Wedad; Walsh, Maureen Y.; Hoey, Susannah E.; O'Kane, Donal
Abstract : Pyoderma gangrenosum (PG) is a rare inflammatory neutrophilic dermatosis often misdiagnosed. It is uncommon in infants and children accounting for 4% of cases. A one-year-old male in paediatric ICU ventilated for bronchopneumonia was referred with ulcerated areas on his neck and axilla corresponding to sites of recent removal of central and arterial lines. Examination revealed areas of deep ulceration with violaceous undermined borders in keeping with PG. This was supported by a skin biopsy showing a neutrophilic infiltrate in the deeper dermis. Topical clobetasol propionate was commenced and a dramatic improvement within 24 hours noted. Blood results showed a leucocytosis of 29.7; a differential WCC showed toxic granulation in neutrophils with myeloid left shift; immunoglobulins showed elevated IgG 23 and IgA 4.86. The elevated WCC made us consider a leukaemic trigger; however, they settled with treatment of the underlying infection. PG in children is more likely to have an atypical distribution involving the head and neck (26.6%) or buttocks (15%). An interesting feature in this case is the presence of pathergy, a term used to describe the induction or exacerbation of PG at sites of iatrogenic or incidental trauma. It is seen in 31% of patients with PG.